2007
DOI: 10.1161/strokeaha.106.477091
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Carotid Artery Stenosis and the Risk of New Vascular Events in Patients With Manifest Arterial Disease

Abstract: for the SMART Study GroupBackground and Purpose-The frequency of asymptomatic carotid artery stenosis (CAS) increases with age from 0.5% in individuals below 50 years of age to 5% to 10% in individuals over 65 years of age in the general population. Its prognostic value has been examined in the general population but less often in patients with clinical manifestations of arterial disease other than retinal or cerebral ischemia. We examined the relationship between asymptomatic CAS and the risk of subsequent ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
125
4
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(141 citation statements)
references
References 25 publications
5
125
4
4
Order By: Relevance
“…13 This finding could be explained by both the reported decline in vascular risk in recent years, possibly related to improved vascular preventive measures, 16,17 and limited access to mortality data in our study.…”
Section: Discussionmentioning
confidence: 70%
“…13 This finding could be explained by both the reported decline in vascular risk in recent years, possibly related to improved vascular preventive measures, 16,17 and limited access to mortality data in our study.…”
Section: Discussionmentioning
confidence: 70%
“…In the past years, several studies have demonstrated that the degree of luminal stenosis represents only one of the parameter that can determine the ischemic stroke and gradually we have evolved to the concept of vulnerable plaque from the concept of risk arising from the degree of stenosis [9,10,107]. However, currently there is a discrepancy between these scientific studies and clinical practice; despite of many publications and discussions, plaque imaging techniques are not really the basics of clinical decision making or current guidelines and in the majority of cases decision towards revascularization are not based on plaque morphology but on the degree of stenosis [108][109][110].…”
Section: Clinical Practice and Results From The Scientific Studiesmentioning
confidence: 99%
“…The implications of risk stratification found by the ACSRS collaborators and other prospective studies 20,29 provide evidence that the vast majority of patients are better off with conservative treatment. Also, patients at higher risk could be identified and offered operative treatment.…”
Section: Natural History Of Asymptomatic Carotid Artery Diseasementioning
confidence: 87%
“…Whilst the outcomes in the symptomatic group are poor if not treated in a timely fashion, the course of ACAD has a low event rate and therefore a much better prognosis. The natural history of ACAD has been extensively studied over the past three decades 10,[12][13][14][15][16][17][18][19][20] . ACAD patients are identified from the presence of cervical bruits, during the investigation of nonspecific signs and symptoms and prior to pre-operative evaluation for cardiac or other major surgery.…”
Section: Natural History Of Asymptomatic Carotid Artery Diseasementioning
confidence: 99%